Takotsubo-Like Left Ventricular Dysfunction in an HIV-Infected Patient - Barbaro, Giuseppe; Pellicelli, Adriano; Barbarini, Giorgio; Akashi, Yoshihiro J. (Current HIV Research, 2006)
Takotsubo cardiomyopathy (in Japanese language
Keywords: Myocarditis